The Meaning of Mauludan Tradition in Local Javanese Islamic Rituals: Between Teachings and Customs - Andrean, Seka; Susanti, Septiani Selly (Mimbar Agama Budaya, 2023)
Islam and tradition are two different substances, but in their manifestations can influence each other, complement each other, and color each other's behavior. The purpose of this study is to explain the meaning of mauludan tradition in local kejawen rituals in Islam and tradition. The research method used with a literature study approach through literature sources from various literature sources about the Mauludan tradition in Islam and Javanese tradition. Then analyzed and presented the results of the data findings objectively. The results showed that the Mawlid tradition is a commemoration of the birthday of the Prophet Muhammad SAW which is held every 12 Rabiul Awal. In welcoming the birth month of the Prophet, Muslims often hold various celebrations that have been passed down to form a tradition. As in Indonesia, many events are held to welcome the month of Mawlid. There are several mauludan traditions in Javanese Islamic rituals, including: Barik'an tradition, meron tradition, grebeg maulud tradition, weh-wehan tradition, ampyang maulid tradition, and sekaten tradition. The meanings or values contained in the mauludan tradition are: spiritual values, moral values, social values, and unity values.